Analisa keausan pahat pada pemesinan bor magnesium AZ31 menggunakan metode taguchi - Gusri Akhyar Ibrahim; Joni Iskandar; Arinal Hamni; Sri Maria Puji Lestari (Badan Kerja Sama Teknik Mesin Indonesia, 2017)
hisel rotating on a workpiece. During the machinery process happenedinteraction between the eye drill with a workpiece where work truncatedwhile a jackhammer experienced friction. Friction experienced a chiselcoming from the surface upset that flows and the surface of a workpiece thathas been lopped off, due to friction this chisel had worn out. The purpose ofthis research will analyzes age use a chisel hss in pemesinan drill magnesiumaz31 and to support the survey used method of taguchi to analyze pembahsanthe results of the study. Machinery parameter a drill that is used namely ajackhammer hss ( hight speed steel with size ( 10 mm, 12 mm, and 14 mm ),the pace lap ( 635 rpm, 970 rpm, 1420 rpm ) and used motion a meal ( 0.10mm / rev, 0.18 mm / rev and 0.24 mm / rev ), with a depth cut 50 mm. thedata wear a chisel carried out using a microscope digital usb with event 50x.Data wear chisel seen every time one drilling process and machinery processwill be stopped if a drill bit has made out. The results showed that chiselhighest age profits to drill diameter 10 mm and the pace lap 635 rpm anduse motion eat 0,10 mm / rev which was during 12,74 minutes, while agechisel lowest diameter drill obtained at 14 mm and the pace lap 1420 rpmand use of motion eat 0,18 mm / rev which was during 0,68 minutes.Basedon analisys of variant ( anova ) that parameter most significant inmempengaruh age wearing a drill bit is the pace lap ( n ). The greater thepace lap ( n ) and wear a drill bit will be more quickly, this is because hightemperatures in the result of friction between screw eyes and workpiece.